WEB-BASED ONLINE EXAM INFORMATION SYSTEM TO IMPROVE THE QUALITY OF LEARNING EVALUATION FOR STUDENTS - Hartatik Hartatik; Suci Wulandari (International Journal of Economy, Education and Entrepreneurship, 2022)
Digitalization currently refers to the use of digital-based systems. The design of the online examination system developed in this research is an online exam information system in elementary schools, more specifically for Integrated Islamic boarding schools (SDIT). The purpose of creating this system is to make it easier for students to move on exams quickly and see evaluations and scores of exam results. The creation of this system design begins with analyzing system needs and making system design in business processes, FR tables, use case diagrams, use case text, and class diagrams. Then proceed with creating a database design in ERD, relationships between tables, and table design. Furthermore, user interface design and system testing design were made using the BlackBox system. The result of this information system design is a Web-Based Online Exam Information System for students who can run exams online and display the scores of exams results that student have